Women’s Intrinsic Motivation in Conducting Breast Self-Examination - Nabila Rahma Nur; Ermiati Ermiati; Atlastieka Praptiwi (Journal of Nursing Care, 2018)
Introduction, early detection of cancer is an important action in addressing the high incidence breast cancer cases. The easiest early detection that women could do is breast self-examination(BSE). Previous research indicated a gap between knowledge and behavior towards breast self-examination. Intrinsic motivation is needed by women to perform breast self-examination. This study aimed to identify the intrinsic motivation of women reproductive age in performing breast self-examination in Kebonwaru District Bandung. Methods, this study was a descriptive quantitative study, the study population was women in reproductive ages. The samples were chosen using the simple random technique (n = 344). Data was collected using Intrinsic Motivation Inventory instrument which has been back-translated. Data were analyzed using descriptive analysis of frequency distribution and percentage. The results showed that the proportion of respondents who had the high intrinsic motivation and low intrinsic motivation were almost the same (54.1% and 45.9% respectively). The majority of respondents (84% of) had a high perception of importance and usability of BSE. 66.3% of respondents had a perception of suitability and interest along with high competence perception. In addition, 56.4% of respondents had a high perception of effort and choice. However, 57.4% of respondents reported an increased sense of stress and nervous when performing BSE. Conclusion, there is a need to maximize cancer prevention and promotion programs.  For example, health education related to cancer prevention and treatment,  accompaniment, and counseling, and providing information about the importance of early detection.  That information could increase the intrinsic motivation of women to perform breast self-examination so a number of women’s mortality caused by breast cancer could be decreased and breast cancers could be detected earlier.